AI, BIG DATA AND THE EVOLUTION OF DIGITAL DIPLOMACY: A TRANSFORMATIVE SHIFT IN 21ST CENTURY FOREIGN POLICY PRACTICE - Zeynalova, Shabnam (Veredas do Direito, 2026)
This study examined the transformative impact of digital technologies—particularly artificial intelligence (AI), big data, and algorithmic systems—on contemporary diplomacy. The primary objective was to conceptualize "algorithmic diplomacy" and analyze its integration into the strategic practices of foreign ministries. Using qualitative content analysis of policy documents and digital communication platforms, the research identified key trends such as real-time decision-making, digital public diplomacy, and crisis management enabled by AI. Findings also highlighted challenges including cybersecurity threats, digital authoritarianism, and ethical opacity. A focused case study on Azerbaijan demonstrated how a Global South nation leveraged AI and digital platforms to modernize its diplomatic infrastructure. The study concluded that digitalization redefined core diplomatic concepts like power and sovereignty. It called for ethical standards and international cooperation to ensure transparent and accountable algorithmic governance in diplomacy.